IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (STUDI KASUS DI DESA DALUNG KECAMATAN KUTA UTARA KABUPATEN BADUNG) - Putu Arista, Maria Yovani; Erviantono, Tedi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2015)
ABSTRAK Dalung village is located in the area of the district Government of North Kuta, Badung Regency. This village is one of the village with the acquisition of the Village Fund Allocation. However, ini 2014 the acquisition of the Village Fund Allocation has decreased, so it can not contribute fully to to the development adn empowerment of rural communities. The purpose of this study isÂ  to investigate the implementation of management policies in Village fund Allocation of Dalung Village in 2014. This study use descriptive qualitative method and the data was collected by observation and interviews technique. The conclusion of this study are as follow: The Village Fund Allocation policy implementation in the Dalung Village already well underway, although there is a decrease in the acquision of the Village Fund Allocation can not contribute fully to the developmentÂ  and empowerment of rural communities. Although it is not able to contribute fully, the used of Village Fund Allocation these must remainded accountable. Therefore, the Badung Regency administration used the program called â€œSIKUDESâ€ (Village Financial System) to assist the village in financial reporting, but there are some problem by using this program. This program is too complicated, and the absence of a binding legal basis, then at the end of 2014, the Government of Building decided to suspend the use of this â€œSIKUDESâ€ program. From the performance of the Government of Dalung Village in the Village Fund Allocation policy implementation was successful. This could be evidenced by never found any cases of fraud or evasion of the Village Fund Allocation. Keyword: Policy Implementation, Village Fund Allocation, Village Financial System (SIKUDES)